Estudo do sistema de drenagem pluvial urbana no bairro Jardim Canadá no município de Goioerê, Paraná - Souza, Lucas de Araújo (2023)
This work aimed to conduct a study of the stormwater drainage network in Jardim Canadá, a neighborhood located in the municipality of Goioerê, Paraná state. The increasing urbanization and rainfall patterns have resulted in various issues related to urban drainage, such as erosion, flooding, and runoff. In this context, urban stormwater drainage plays a crucial role in the infraestructure of cities and ensuring social wellbeing. To achieve the proposed objectives, information about the existing drainage network was collected through projects, maps, and on-site visite. The contributing areas that influence the drainage network, along with their corresponding flow rates, were calculated. Possible additional flows to the network were also analyzed, and the capacity of the drainage system was assessed using the rational method. The results revealed significant challenges in the Jardim Canadá drainage network. Even without considering the additional flows, overloads and high velocities were indentified in some sections. With the inclusion of the additional flows, the problems worsened, highlighting bottlenecks and overloads at the beginning of the network. In conclusion, continuos investments in urban drainage infrastructure are essential to ensure a robust and efficient system capable of adequality handling the demands of urban areas and preventig issues such as vector proliferation and property devaluation.